Flow and heat transfer past a permeable power-law deformable plate with orthogonal shear in a hybrid nanofluid - Khashi'ie, Najiyah Safwa; Md Arifin, Norihan; Pop, Ioan; Nazar, Roslinda; Hafidzuddin, Mohd Ezad Hafidz; Wahi, Nadihah (Elsevier, 2020)
This study concerns the three-dimensional hybrid nanofluid flow and heat transfer due to a deformable (stretching/shrinking) plate with power-law velocity and orthogonal surface shear. The flow due to the shrinking sheet is maintained with the imposition of wall mass suction. The effect of adding Cu and Al2O3 nanoparticles are represented by a homogeneous mixture model with the modified thermophysical properties. Two types of thermophysical properties for hybrid nanofluids are discussed and compared in this interesting work. The three-dimensional model is then, reduced into a relevant set of ordinary differential equations using similarity transformation. The results are generated using the bvp4c solver and presented in the tables and graphs. Duality of solutions are observed in both stretching and shrinking regions, however, only the first solution is proved to be stable and realistic. Surprisingly, the heat transfer rate augments when the power law velocity is used. The hybrid nanofluid with an upsurge of copper volume fraction also reduces the rate of heat transfer.